O albinismo e seus paradoxos : reflexões epistemológicas sobre os processos identitários das pessoas albinas no estado de Mato Grosso - Melo, José Adailton Vieira Aragão (2024)
ABSTRACT: Some societies are marked by stereotypical and exclusionary views of some social groups, including the albino population in the state of Mato Grosso and the complexity of constructing their identities. Thus, this work, supported by interdisciplinary and, above all, cultural approaches, immerses itself in this “universe” in an attempt to deconstruct stigmatizing ideas and promote the recognition of this group, investigating and, at the same time, seeking to understand the paradox of albino identity. The research problem is the search to unravel the “enigmatic white” and the possible “stigmatized identity”, based on the work of Chelala (2007) and the relationship with the identity of the albino person, and, to what extent can we affirm the existence of the “stigmatized identity”, permeated by some social markers of difference, such as: health/disease, race/ethnicity and color. Still based on this, are we facing “unclassifiable being” defended by the author? As a theoretical framework, we have the contributions of: Goffman (1975) and his work on stigma, also marked on the skin and how much this affects the albino population. On body, race/ethnicity and the struggle for recognition, we have as a basis Le Breton (2003); Munanga (2004, 2017); Kilomba (2004); Spivak (2010); Bhaba; Gonzales (2022) and Honneth (2003). To discuss the construction of identity, it is relevant to think about political, social and cultural factors, based on the ideas of Eder (2003); Hall (2003); Silva (2014) among others. We also have colorism/pigmentocracy and its relationship with albino identity, through the highlighted contributions of Walker (1983); Vainer (2020) and Müller (2018), inviting us to reflect on the social hierarchy based on color, which generates contradictions when thinking about the color “albino white”. The methodological design was exploratory and qualitative, with the application of semi-open questionnaires and virtual interviews (Google Meet) that allowed us to collect relevant data for research. I also used an application (WhatsApp) in informal conversations, enabling more direct contact and enriching communication for the construction of the thesis. As results/discussions: the analysis of the data demonstrates the relevance of investigating the collective and individual identity processes of the albino population in question. Stigma manifests itself in different ways, shaping the “perception of oneself and the Other”, yet we have the State, Science and Western discourses exerting influence on the process of constructing the albino identity, affecting the way they see themselves, others and how they are seen by non-albino people. In conclusion: one can consider a “stigmatized identity”, the fight for recognition or “horizon of identity recognition” and public policies that aim to propose positive visibility and that become the main agendas of the albino community in the state of Mato Grosso.